1995
DOI: 10.20870/productions-animales.1995.8.2.4115
|View full text |Cite
|
Sign up to set email alerts
|

Emploi des liants pour le pressage des aliments des animaux : aspects technologiques et nutritionnels

Abstract: Les liants (ou adjuvants de pressage) sont des additifs généralement dépourvus de valeur alimentaire qui sont incorporées à faible taux (0,5 à 2,5 %) dans les aliments composés dans le seul but d’augmenter le rendement des presses et la cohésion des granulés. Ces substances peuvent être d’origine organique ou minérale. Parmi les substances organiques, les lignosulfites sont des sous-produits de l’industrie papetière. Les substances minérales appartiennent essentiellement à la famill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…NIR reflectance is sensitive to physico-chemical characteristics found in raw materials and cereal grains ( Pasikatan et al, 2001 ). Although experiment 1 was designed to evaluate the effects of methodologies on mixer performance, previous research has demonstrated that particle size and variation in nutrient profile of ingredients have an impact on the reported chemical composition of feed analyzed by NIR equipment (Mel-cion, 1974 ; Norris and Barnes, 1976 ; Pedamond, 1977 ; Williams and Starkey, 1980 ; Nathier-Dufour et al, 1995 ). Since the readings of the NIR are affected by the geometry of the particles, the particle size effects on spectra may be considered “noise,” thus the samples collected must be uniformly ground ( Wendtlandt and Hecht, 1966 ; Pasikatan et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…NIR reflectance is sensitive to physico-chemical characteristics found in raw materials and cereal grains ( Pasikatan et al, 2001 ). Although experiment 1 was designed to evaluate the effects of methodologies on mixer performance, previous research has demonstrated that particle size and variation in nutrient profile of ingredients have an impact on the reported chemical composition of feed analyzed by NIR equipment (Mel-cion, 1974 ; Norris and Barnes, 1976 ; Pedamond, 1977 ; Williams and Starkey, 1980 ; Nathier-Dufour et al, 1995 ). Since the readings of the NIR are affected by the geometry of the particles, the particle size effects on spectra may be considered “noise,” thus the samples collected must be uniformly ground ( Wendtlandt and Hecht, 1966 ; Pasikatan et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%